Associations between pre-, post-, and peri-operative variables and health resource use following surgery for head and neck cancer. (March 2019) - Badr, Hoda; Sobrero, Maximiliano; Chen, Joshua; Kotz, Tamar; Genden, Eric; Sikora, Andrew G.; Miles, Brett
Highlights: Pre-, post-, and peri-operative variables predicting health resource use were examined . Pre-surgical QOL significantly predicted length of stay (LOS). Pre-surgical dysphagia predicted LOS, readmissions, and emergency room visits. Pre-surgical dysphagia and QOL assessment may help identify at-risk patients. Abstract: Objective: We examined associations between pre-, post-, and peri-operative variables and health resource use in head and neck cancer patients. Methods: Patients (N = 183) who were seen for a pre-surgical consult between January 2012 and December 2014 completed surveys that assessed medical history, a patient-reported outcome measure (PROM) of dysphagia, and quality of life (QOL). After surgery, peri-operative (e.g., tracheostomy, feeding tube) and post-operative (e.g., complications) variables were abstracted from patients' medical records. Results: Multivariate regression models using backward elimination showed that pre-surgical University of Washington Quality of Life (UW-QOL) Inventory and M.D. Anderson Dysphagia Inventory (MDADI) composite scores, documented surgical complications, and having a tracheostomy, were all significant predictors of hospital length of stay, explaining 57% of the total variance (F(5, 160) = 18.71, p < .001). Male gender, psychiatric history, and lower pre-surgical MDADI scores significantly predicted thirty-day unplanned readmissions (30dUR). Pre-surgical MDADI composite scores also significantly predicted emergencey department (ED) visits within 30 days of initial hospital discharge (p = .02). Conclusions: Assessment of PROMs and QOL in the pre-surgical setting may assist providers in identifying patients at risk for prolonged LOS and increased health resource use after hospital discharge.